2008
DOI: 10.1080/03079450701802206
|View full text |Cite
|
Sign up to set email alerts
|

Beak and feather disease virus infection in cockatiels (Nymphicus hollandicus)

Abstract: Psittacine beak and feather disease is known to occur in a wide range of psittacine species; however, there are no scientific or credible anecdotal reports of psittacine beak and feather disease occurring in the cockatiel (Nymphicus hollandicus) despite it being one of the world's most commonly kept companion bird species. Consequently, this has resulted in speculation that the species may have some innate resistance to beak and feather disease virus (BFDV) infection. To investigate this hypothesis we conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…BFDV DNA was detected in a symptomatic Blue-and-Yellow macaw (Table 2). Although there are few reports available on the incidence of BFDV in Brazil, the virus has been described in other continents (Pass & Perry, 1984;Shearer et al, 2008). In our study, swab and blood samples were collected at arrival of the birds at the triage centers, avoiding contact with resident birds.…”
Section: Molecular Diagnosis Of Beak and Feather Disease In Native Brmentioning
confidence: 99%
See 2 more Smart Citations
“…BFDV DNA was detected in a symptomatic Blue-and-Yellow macaw (Table 2). Although there are few reports available on the incidence of BFDV in Brazil, the virus has been described in other continents (Pass & Perry, 1984;Shearer et al, 2008). In our study, swab and blood samples were collected at arrival of the birds at the triage centers, avoiding contact with resident birds.…”
Section: Molecular Diagnosis Of Beak and Feather Disease In Native Brmentioning
confidence: 99%
“…present lower incidence of the disease compared with Old World species (Eclectus sp., Agapornis sp.) (Shearer et al, 2008;Piçarra, 2009). Although BFDV was detected in Amazona aestiva individuals in the present study, the birds were asymptomatic, in agreement with a previous report (Piçarra, 2009).…”
Section: Molecular Diagnosis Of Beak and Feather Disease In Native Brmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cross-reactivity work 7 using sera from rainbow lorikeets, short-billed corellas, a sulphur-crested 8 cockatoo, a red lory (Eos bornea) and a galah-corella hybrid and virus from 9 rainbow lorikeets, a red lory, two swift parrots (Lathamus discolor), a sulphur-10 crested cockatoo and a scarlet-chested parrot (Neophema splendida) failed to 11 find evidence of antigenic serotypes (Khalesi et al, 2005). However, a similar 12 experiment using sera from the above birds and virus eluted from the feather 13 of a cockatiel found that sera from some of the birds did not inhibit 14 agglutination by the cockatiel isolate, suggesting that the cockatiel isolate may 15 be sufficiently different antigenically to be considered a separate serotype 16 (Shearer et al, 2008a). 17…”
mentioning
confidence: 99%
“…In total, 160 samples 7 were thus collected. In addition, samples from 82 cockatiels known to be HI 8 negative (Shearer et al, 2008a) were included to evaluate the diagnostic 9 specificity of the test. Samples included both dried blood on filter paper and 10…”
mentioning
confidence: 99%